ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) BERKELANJUTAN MENGGUNAKAN METODE UTAUT 2 PADA MAHASISWA UNIVERSITAS DIPONEGORO - Davina Najwaa Hanifah; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This research was conducted with the aim of analyzing the factors that influence the behavioral intention and use behavior of QRIS among students at Diponegoro University. This research uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) framework introduced by Venkatesh et al. (2012), extended with the Digital Financial Literacy variable. There are 8 constructs that form this research framework, namely performance expectancy, effort expectancy,social influence, facilitating conditions, hedonic motivation, price value, habit, and digital financial literacy, along with 2 other factors, namely behavioral intention and use behavior of QRIS. This research population involves active students of Diponegoro University from the class of 2022-2024 with a research sample of 430 respondents obtained through purposive sampling. Data collection was carried out through an online survey using questionnaires, and the data were analyzed using the Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach with the help of SmartPLS 4.0 software. The research results show that six hypotheses in this study are accepted. Performance expectancy,facilitating conditions, hedonic motivation, price value, and habit have a significant positive effect on the behavioral intention to use QRIS, and behavioral intention was found to have a significant positive effect on the actual use behavior of QRIS. However, effort expectancy, social influence, and digital financial literacy have no significant effect on the behavioral intention of QRIS users. Furthermore, it is known that habit, hedonic motivation, and behavioral intention are the most significant determinants among other factors, with a p-value of 0.000.